(untitled) (Bulletin KNOB, 2002)
In the period 1945-1963 1564 new churches and chapels were built in the Netherlands. Also from an international point of view, this is an enormous number, which is not just to be accounted for by the destruction during the war and the increase in population. Consequently, churches were at the centre of a civilisation offensive, combined with the district approach trying to found well-organised and socially-minded communities again. Initially a considerable distinction in tradition, liturgy, rules and style existed between the Roman-Catholic and the Protestant churches, but eventually a large degree of convergence developed. Four churches are discussed in greater detail, because they shed a different light on the architecture discourse between the New Building and the so-called traditionalists of the Delft School. The Roman-Catholic church of Our Lady of Perpetual Aid for the district De Heuvel in Breda is one of the few executed designs of Prof. Ir. M.J. Granpré Molière, the undisputed leader of the Delft School. He wants the church to crown a district, but also to maintain its distance from the profane at ‘its own grounds’. The major instrument to achieve this is the facade. Upon closer consideration it was found that this church does not fit in with the tradition of Dutch churches, but incorporates many different international traditions and themes, without directly copying them. Nevertheless, the urban ensemble realised here by Granpré no longer seems to be the answer to the broader and larger-scale practice of the Reconstruction. However, Van den Broek and Bakema do seem to seek this answer in the North Holland Resurrection church for the district Zielhorst in Schiedam. Immediately after its construction this church, mainly built in concrete and glass, already evoked mixed feelings. Van den Broek, who was involved in drawing up the rules for the building of the Reformed Churches, is not able to meet all his own rules here, nor does he produce any conclusive proof yet that church building in an utterly modern form is acceptable to a lot of users. In the village of Nagele in the new North East polder they try to build a modern church once again. In this example, by way of a spiral composition, both the experience of the spaciousness of the polder and of shelter and seclusion, but with heavenly light, are possible. Bakema states to have sought the same transcendence as Granpré Molière with different means. The Roman-Catholic Pastoor Van Ars church in the district Loosduinen in The Hague does not resemble a traditional church at all, but through spatial associations with a Gothic nave and a (Roman) crypt Aldo van Eyck explicitly wishes to evoke a religious experience in a ’post-religious’ era. Even the forever fiercely arguing ’youngsters’ of Team X, who were opposed to the old ’New Building’ were silenced when they saw this church.